2019
DOI: 10.3389/fimmu.2019.02748
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Features of Canine Non-conventional CD4−CD8α− Double-Negative TCRαβ+ vs. TCRγδ+ T Cells

Abstract: The role of conventional TCRαβ+CD4+ or TCRαβ+CD8α+ single-positive (sp) T lymphocytes in adaptive immunity is well-recognized. However, non-conventional T cells expressing TCRαβ or TCRγδ but lacking CD4 and CD8α expression [i.e., CD4−CD8α− double-negative (dn) T cells] are thought to play a role at the interface between the innate and adaptive immune system. Dn T cells are frequent in swine, cattle or sheep and predominantly express TCRγδ. In contrast, TCRγδ+ T cells are rare in dogs. In this study, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 62 publications
(70 reference statements)
6
25
0
Order By: Relevance
“…In contrast to reports for frequencies of healthy human CD25+ CD4+ T cell ( 68 , 69 ), our studies revealed a higher frequency of this subset within both healthy controls and patients which proved to include both FoxP3- as well as FoxP3+ cell populations. Other reports describing CD25+ cell frequencies within the CD4+ T cell subset in healthy dogs also revealed similar or higher frequencies compared to our current studies ( 44 , 70 , 71 ). Our results also revealed increased frequencies of the CD25+ cells for both CD4+ and CD4-CD8- T cell subsets in canine melanoma patients compared to healthy dog controls.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In contrast to reports for frequencies of healthy human CD25+ CD4+ T cell ( 68 , 69 ), our studies revealed a higher frequency of this subset within both healthy controls and patients which proved to include both FoxP3- as well as FoxP3+ cell populations. Other reports describing CD25+ cell frequencies within the CD4+ T cell subset in healthy dogs also revealed similar or higher frequencies compared to our current studies ( 44 , 70 , 71 ). Our results also revealed increased frequencies of the CD25+ cells for both CD4+ and CD4-CD8- T cell subsets in canine melanoma patients compared to healthy dog controls.…”
Section: Discussionsupporting
confidence: 90%
“…Data generated from these studies of canine melanoma patients afforded an opportunity to analyze different canine T cell subsets and subpopulations for specific T cell markers based on healthy control dogs. An interesting CD4-CD8- CD3+ T cell subset was reported and characterized previously to express regulatory markers including FoxP3 and CD25 ( 44 ). Our results for 20 healthy control dogs also show FoxP3 expression by CD4-CD8- T cells although frequencies of FoxP3+ cells for this subset are lower compared to CD4+ cells with a difference trending for significance ( p = 0.052) ( Figure 8A ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, it may be of interest that the percentage of DN T lymphocytes found both in cardiac patients and healthy dogs in our study was much higher than in healthy mice and humans, which typically have <5% of DN T‐cells 37,38 . Two studies in healthy dogs 39,40 also found a high percentage of DN T lymphocytes in peripheral blood, approximately 10% in 1 study 39 and 15% in another study 40 . The reason for this species‐specific difference remains to be investigated.…”
Section: Discussionmentioning
confidence: 61%